MACROD2 gene associated with autistic-like traits in a general population sample - Jones, R.; Cadby, G.; Blangero, J.; Abraham, L.; Whitehouse, A.; Moses, Eric (2014)
There is now substantial evidence that autistic-like traits in the general population lie on a continuum, with clinical autism spectrum disorders (ASD) representing the extreme end of this distribution. In this study, we sought to evaluate five independently identified genetic associations with ASD with autistic-like traits in the general population. In the study cohort, clinical phenotype and genomewide association genotype data were obtained from the Western Australian Pregnancy Cohort (Raine) Study. The outcome measure used was the Autism Spectrum Quotient (AQ), a quantitative measure of autistic-like traits of individuals in the cohort. Total AQ scores were calculated for each individual, as well as scores for three subscales. Five candidate single nucleotide polymorphism (SNP) associations with ASD, reported in previously published genomewide association studies, were selected using a nominal cutoff value of P less than 1.0×10. We tested whether these five SNPs were associated with total AQ and the subscales, after adjustment for possible confounders. SNP rs4141463 located in the macro domain containing 2 (MACROD2) gene was significantly associated with the Communication/Mindreading subscale. No other SNP was significantly associated with total AQ or the subscales. The MACROD2 gene is a strong positional candidate risk factor for autistic-like traits in the general population.